2005
DOI: 10.1002/bsl.664
|View full text |Cite
|
Sign up to set email alerts
|

Nipping psychopathy in the bud: an examination of the convergent, predictive, and theoretical utility of the PCL‐YV among adolescent girls

Abstract: Over the last decade rates of violence among adolescent girls have increased. Within high-risk contexts, urgent calls for assessment options have resulted in the extension of adult and male-based instruments to adolescent females in spite of the absence of strong empirical support. The current study evaluates the downward extension of psychopathy within a population of female juvenile offenders (N ¼ 125). The convergent and predictive validity of the Psychopathy Checklist-Youth Version (PCL-YV) were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 62 publications
6
79
2
1
Order By: Relevance
“…Salekin et al (1998), for instance, in their study of female offenders found that Factor 1 demonstrated a significant association with recidivism; whereas, the relationship between Factor 2 and recidivism was negligible. This is consistent with suggestions that interpersonal and affective traits of psychopathy are particularly salient factors for women and their risk of reoffending (Odgers et al, 2005).…”
Section: Recidivism and Psychopathysupporting
confidence: 91%
See 1 more Smart Citation
“…Salekin et al (1998), for instance, in their study of female offenders found that Factor 1 demonstrated a significant association with recidivism; whereas, the relationship between Factor 2 and recidivism was negligible. This is consistent with suggestions that interpersonal and affective traits of psychopathy are particularly salient factors for women and their risk of reoffending (Odgers et al, 2005).…”
Section: Recidivism and Psychopathysupporting
confidence: 91%
“…The predictive validity of psychopathy for female adolescents has, however, been questioned, with effect sizes being reported that fail to reach statistical significance, and considerably smaller than those reported in the adult male literature (e.g., Edens et al, 2007;Odgers et al, 2005). There is also some evidence that female psychopaths are less aggressive and violent than their male counterparts (Mulder et al, 1994), and may begin offending later in life (Hart and Hare, 1997).…”
Section: Psychopathy and Gendermentioning
confidence: 99%
“…Due to the limited sample size for adolescent girls (n = 184), as well as concerns about assessing psychopathy among female youths (Odgers, Reppucci, & Moretti, 2005;Vin cent, Odgers, McCormick, & Corrado, 2008), it was not feasible or appropriate to include them in the present study. The adolescent males self-identified as African American (42.14%), Hispanic (34.01%), and Caucasian (19.23%), with a small percentage of other races (4.61%).3 Although there were more African Ameri cans in Philadelphia and more Hispanics in Phoenix, there were no substantial differences on key variables (age, number of priors, and age at first prior) between the two study sites (see Table 1).…”
Section: Methods Participantsmentioning
confidence: 98%
“…Although there are few studies of psychopathic features among adolescent females, one study reported a pattern of correlates of PCL:YV scores similar to that reported for males (Bauer & Kosson, 2000), including criminal activity, institutional misconduct, and externalizing psychopathology. The only other prior study reported that, among incarcerated adolescent females, PCL:YV scores were related to concurrent physical aggression (Odgers, Reppucci, & Moretti, 2005), but links between psychopathy and aggression were attributable to victimization experiences, a finding not previously reported in males. However, the construct validity of psychopathy in adolescent females is less well established.…”
Section: Psychopathy In Adolescentsmentioning
confidence: 95%